2016
DOI: 10.3758/s13414-016-1073-z
|View full text |Cite
|
Sign up to set email alerts
|

Categorical information influences conscious perception: An interaction between object-substitution masking and repetition blindness

Abstract: The visual system is constantly bombarded with dynamic input. In this context, the creation of enduring object representations presents a particular challenge. We used object-substitution masking (OSM) as a tool to probe these processes. In particular, we examined the effect of target-like stimulus repetitions on OSM. In visual crowding, the presentation of a physically identical stimulus to the target reduces crowding and improves target perception, whereas in spatial repetition blindness, the presentation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 86 publications
(126 reference statements)
1
8
0
Order By: Relevance
“…The presence and position of distractors, or other display elements, can modulate the intensity with which OSM occurs, even when such elements are some distance from the location of the target. Our claim that OSM is dependent on non-local factors is in some respects similar to recently reported findings by Goodhew, Greenwood and Edwards (2016). These authors showed that the presence of a repeated stimulus of the same categorical type would affect OSM even though the repeated stimulus item was located some distance from the target on the viewed display.…”
Section: Resultssupporting
confidence: 91%
“…The presence and position of distractors, or other display elements, can modulate the intensity with which OSM occurs, even when such elements are some distance from the location of the target. Our claim that OSM is dependent on non-local factors is in some respects similar to recently reported findings by Goodhew, Greenwood and Edwards (2016). These authors showed that the presence of a repeated stimulus of the same categorical type would affect OSM even though the repeated stimulus item was located some distance from the target on the viewed display.…”
Section: Resultssupporting
confidence: 91%
“…Other researchers have demonstrated that even during OSM, information from other objects like shapes (Prime, Pluchino, Eimer, Dell'acqua, & Jolicoeur, 2011;Woodman & Luck, 2003) and arrows (Chen & Treisman, 2009) can still be processed with enough strength to influence attention. Semantic processing (Goodhew, Visser, Lipp, & Dux, 2011) and categorization of letters (Goodhew, Greenwood, & Edwards, 2016) is known to persist as well. Processes, such as feature integration, also might occur during OSM (Chakravarthi & Cavanagh, 2009; although see Gellatly et al, 2006;Jacoby et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Repetition blindness. OSM interacts with repetition blindness (Goodhew, Greenwood, & Edwards, 2016). Repetition blindness refers to the discovery that repeating the identity of a stimulus close in time can impair the individuation of a unique episodic representation for both instances (Kanwisher, 1987).…”
Section: The Relationship Between Osm and Other Visual-cognitive Phenmentioning
confidence: 99%